The Effect of Seasonal Flood on Agricultural and Industrial Land Values in Malaysia: A Hedonic Pricing Model (HPM) Approach. - Ismail, Nur Hafizah; Abdul Karim, Abdul Malek; Basri, Bakti Hasan (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2017)
Flood disasters have raised critical issues for landowners as they might affect land values. The argument of possible decline in the value of land located in flood-liable areas has been discussed in previous literature. However, existing studies on flood impact in Malaysia are few and do not focus on land property as a main issue of study. Therefore, in this study, we investigate the effect of flood on agricultural and industrial land property values in Malaysia by using the Hedonic Pricing Model (HPM). The results of this study suggest that flood duration significantly reduced the value of agricultural and industrial land property. The results from this study has benefits for landowners in terms of understanding the effect of flood duration on agricultural and industrial land values and factors responsible for decreasing land value. This will help the landowners to make contingency arrangement on the property assets to ensure that loss due to flood is minimized.